Tuning the Properties and Self-Healing Behavior of Ionically Modified Poly(isobutylene-co-isoprene) Rubber - Suckow, Marcus; Mordvinkin, Anton; Roy, Manta; Singha, Nikhil K.; Heinrich, Gert; Voit, Brigitte; Saalwaechter, Kay; Boehme, Frank (Macromolecules, 2018)
The focus of this work is on the nature of self-healing of ionically modified rubbers obtained by reaction of brominated poly(isobutylene-co-isoprene) rubber (BIIR) with various alkylimidazoles such as 1-methylimidazole, 1-butylimidazole, 1-hexylimidazole, 1-nonylimidazole, and 1-(6-chlorohexyl)-1H-imidazole. Based on stress-strain and temperature dependent DMA measurements, a structural influence of the introduced ionic imidazolium moieties on the formation of ionic clusters and, as a consequence, on the mechanical strength and self-healing behavior of the samples could be evidenced. These results are fully supported by a molecular-level assessment of the network structure (cross-link and constraint density) and the dynamics of the ionic clusters using an advanced proton low-field NMR technique. The results show distinct correlations between the macroscopic behavior and molecular chain dynamics of the modified rubbers. In particular, it is shown that the optimization of material properties with regard to mechanical and self-healing behavior is limited by opposing tendencies. Samples with reduced chain dynamics exhibit superior mechanical behavior but lack on self-healing behavior. In spite of these limitations, the overall performance of some of our samples including self-healing behavior exceeds distinctly that of other self-healing rubbers described in the literature so far.
CRIS-Team Scopus Importer:2022-04-14